Твердосмазочные композиты на основе сверхвысокомолекулярного полиэтилена (СВМПЭ) - Буслович Д. Дмитрий; Панин С. В. Сергей Викторович; Корниенко Л. А. Людмила Александровна; Алексеенко В. О. Владислав Олегович; Валентюкевич Н. Н. Наталья Николаевна (2017, 2017)
Заглавие с экрана